Long-term O3–precursor relationships in Hong Kong: field observation and model simulation - Y. Wang; Y. Wang; H. Wang; H. Wang; H. Guo; X. Lyu; H. Cheng; Z. Ling; P. K. K. Louie; I. J. Simpson; S. Meinardi; D. R. Blake (Atmospheric Chemistry and Physics, 2017)
Over the past 10 years (2005–2014), ground-level O3 in Hong Kong has consistently increased in all seasons except winter, despite the yearly reduction of its precursors, i.e. nitrogen oxides (NOx =  NO + NO2), total volatile organic compounds (TVOCs), and carbon monoxide (CO). To explain the contradictory phenomena, an observation-based box model (OBM) coupled with CB05 mechanism was applied in order to understand the influence of both locally produced O3 and regional transport. The simulation of locally produced O3 showed an increasing trend in spring, a decreasing trend in autumn, and no changes in summer and winter. The O3 increase in spring was caused by the net effect of more rapid decrease in NO titration and unchanged TVOC reactivity despite decreased TVOC mixing ratios, while the decreased local O3 formation in autumn was mainly due to the reduction of aromatic VOC mixing ratios and the TVOC reactivity and much slower decrease in NO titration. However, the decreased in situ O3 formation in autumn was overridden by the regional contribution, resulting in elevated O3 observations. Furthermore, the OBM-derived relative incremental reactivity indicated that the O3 formation was VOC-limited in all seasons, and that the long-term O3 formation was more sensitive to VOCs and less to NOx and CO in the past 10 years. In addition, the OBM results found that the contributions of aromatics to O3 formation decreased in all seasons of these years, particularly in autumn, probably due to the effective control of solvent-related sources. In contrast, the contributions of alkenes increased, suggesting a continuing need to reduce traffic emissions. The findings provide updated information on photochemical pollution and its impact in Hong Kong.